Massive tuberculous exudative pericarditis under the guise of hydropericardium in a patient with non-compaction cardiomyopathy: diagnosis and treatment - O. V. Blagova; I. N. Alieva; P. V. Senchikhin; L. D. Nazarova; S. V. Chernyavsky; G. Yu. Sorokin; E. V. Pavlenko; V. P. Sedov; N. V. Gagarina; N. D. Sarkisova (Российский кардиологический журнал)
The first presentation of the combination of non-compaction cardiomyopathy  with a restrictive-dilated phenotype  and massive chronic tuberculous pericarditis, which for a long time was under  the guise  of hydropericardium  in congestive  heart  failure in a patient of 30 years, is performed. The absence of congestion signs in a large circle of blood circulation became the reason  for diagnosis of agnogenic  pericarditis and pericardial puncture.  A large volume (>1 l) and lymphocytic nature of effusion, its bilateral character, post-tuberculous changes and calcifications in the lungs, and intrathoracic lymphadenopathy  testified  in favor of the tuberculous  etiology of the process. The negative result of all laboratory tests  for tuberculosis  (Diaskintest, exudate  PCR test, fluorescence microscopy, inoculation on liquid media, Ziehl-Neelsen stain) and the high risk of thoracoscopic biopsy did not allow to immediately verify the diagnosis.  It was made only after repeated elimination of 3,5 l of hemorrhagic exudate and the detection of mycobacterial DNA by PCR. As a result of quadruple tuberculostatic therapy, a remission of the process was achieved (there is no fluid in the pericardial cavity).